The Use of Fresh Cogongrass as Transportation Media with Level Dry System for Broodstock of Crayfish on Various Old Time - Ferdinand Hukama Taqwa; Yulisman - -; I. S. Yulian (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
The research was to determine the effect of the use of fresh cogongrass as media packaging filler on survival rate of broodstock of crayfish that transported with level dry system for 24, 48, dan 72 hours which randomized completely design experiment. The research preparation were media preparation of pond water, preparation of filler material and preparation of experimental animal (3 days adaptation after arrived from producer and starvation for 24 hours). The major research were anestetion of broodstock of crayfish with direct sock of low temperature at 12oC for ±5 minutes, transportation experiment of broodstock with fresh cogongrass as material filler. The result showed that the use of fresh cogongrass on various old time of dry level system has a significantly different to time of recovery and survival rate of broodstock of crayfish after tranforted. The fastest time of recovery was 89.55 seconds for 24 hours transportation and significantly different with time of transportation for 48 hours and 72 hours. The survival rate after tranported the highest was 98.89% for 24 hours transportation and significantly different with time of transportation for 48 hours and 72 hours. This research showed that the use of fresh cogongrass as material packaging filler of dry level system was still effective until 48 hours.Keywords: afresh cogongrass, broodstock of crayfish, various old time transportation, level dry system